Safety and Effectiveness of Arginine in Adults. Issue 12 (9th November 2016) - McNeal, Catherine J; Meininger, Cynthia J; Reddy, Deepika; Wilborn, Colin D; Wu, Guoyao
Abstract: L-Arginine (Arg) appears to have a beneficial effect on the regulation of nutrient metabolism to enhance lean tissue deposition and on insulin resistance in humans. The observed safe level for oral administration of Arg is ∼20 g/d, but higher levels have been tested in short-term studies without serious adverse effects; however, more data are needed in both animal models and humans to fully evaluate safety as well as efficacy. The primary objective of this review is to summarize the current knowledge of the safety, pharmacokinetics, and effectiveness of oral Arg in adults. Arg supplementation has been used safely in vulnerable populations, such as pregnant women, preterm infants, and individuals with cystic fibrosis. Several recent studies have shown beneficial effects of Arg in individuals with obesity, insulin resistance, and diabetes. Collectively, the data suggest that Arg supplementation is a safe and generally well-tolerated nutriceutical that may improve metabolic profiles in humans.